A Method for Source-Microphone Range Estimation in Reverberant Environments Using Arrays of Unknown Geometry. (30th December 2007) - McCarthy McCarthy, Denis Denis; Boland Boland, Frank Frank
Abstract : This paper proposes a technique for determining the distance between a sound source and the microphones in an array. The proposed "Range-Finder" algorithm is robust in the presence of reverberation and, in contrast with previously published source-localization techniques, does not require knowledge of the relative positions of the microphones. We discuss the factors affecting the accuracy of our range estimates and present the results of experiments using simulated and real data to demonstrate the efficacy of our approach.